Decellularization of rat adipose tissue, diaphragm, and heart: a comparison of two decellularization methods - SESLİ, Melis (Turk J Biol, 2018)
Decellularization is a process that involves the removal of cellular material from the tissues and organs while maintaining the structural, functional, and mechanical properties of extracellular matrix. The purpose of this study was to carry out decellularization of rat adipose tissue, diaphragm, and heart by using two different methods in order to compare their efficiency and investigate proliferation profiles of rat adipose-tissue-derived mesenchymal stem cells (AdMSCs) on these scaffolds. Tissues were treated with an optimized detergent-based decellularization (Method A) and a freeze-and-thaw-based decellularization (Method B). AdMSCs were then seeded on scaffolds having a density of 2 × 10(5) cells/scaffold and AO/PI double-staining and MTT assays were performed in order to determine cell viability. In this study, which is the first research comparing two methods of decellularization of an adipose tissue, diaphragm, and heart scaffolds with AdMSCs, Method A provided efficient decellularization in these three tissues and it was shown that these porous scaffolds were cyto-compatible for the cells. Method B caused severe tissue damage in diaphragm and insufficient decellularization in heart whereas it also resulted in cyto-compatible adipose tissue scaffolds.